Flagship D : important facts and details on Eastern Gate Development - Pihak Berkuasa Wilayah Pembangunan Iskandar; Iskandar Regional Development Authority (Johor Bahru : Pihak Berkuasa Wilayah Pembangunan Iskandar, 2008)
PRZSL